2022
DOI: 10.1002/dev.22264
|View full text |Cite
|
Sign up to set email alerts
|

Maternal prolactin levels during late pregnancy and nurturing behavior of offspring in mice

Abstract: Elucidating the mechanisms underlying nurturing and neglect behaviors is meaningful but challenging. Recently, we found that CIN85-deficient mice had reduced pituitary hormone prolactin secretion during late pregnancy, and their pups later showed an inhibited nurturing behavior. To examine whether this phenomenon could be reproduced in normal mice and not just CIN85-deficient mice, we investigated the nurturing behavior of offspring born to mothers whose blood prolactin levels had been reduced by bromocriptine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…The PRL secretion patterns were almost identical to previous studies (Fig. 1B) [11,19] However, our results for PRL3B1 significantly conflicted with those of Soares and Talamantes, where their study showed a plateau in serum PRL3B1 levels from G14 until delivery [11], we detected a sharp decline (Fig. 1A).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The PRL secretion patterns were almost identical to previous studies (Fig. 1B) [11,19] However, our results for PRL3B1 significantly conflicted with those of Soares and Talamantes, where their study showed a plateau in serum PRL3B1 levels from G14 until delivery [11], we detected a sharp decline (Fig. 1A).…”
Section: Discussionsupporting
confidence: 76%
“…In mice, luteolysis is triggered by prostaglandin F2α (PGF2α), reducing the expression of PRLR in the corpus luteum [62,63]. Hence, a high PRL3B1 plasma concentration or the exogenous PRL injection cannot prevent luteolysis, the P4 decline, and parturition [19,64]. Our results (Figs.…”
Section: Endocrine Journal Advance Publicationmentioning
confidence: 68%
See 1 more Smart Citation
“…With dynamic changes in placental lactogen production occurring throughout pregnancy, 51 it is possible that differences between DIO and control pregnant mice were not detectable with sampling at a single time point in the present study. While it has been shown that prolactin levels rise in late pregnancy in the mouse, 58 this is the first study to examine serial prolactin levels in the peripartum and determine changes in prolactin concentrations relating to time of birth in mice. Similar to rats (reviewed in Phillipps et al 17 ), mice have a pre‐partum prolactin surge, and in mice this started approximately 18 h before birth and decreased between 3 h pre‐birth and 6 h post‐birth.…”
Section: Discussionmentioning
confidence: 98%
“…It was summarized that prolactin from the dam may activate certain neural circuits in the fetus that are required for the expression of certain maternal behavioral characteristics such as nurturing ability when fully mature [ 124 ]. However, more recent work by these same authors aimed to emulate this study by artificially lowering prolactin concentrations during pregnancy, and unfortunately did not find the same relationships [ 133 ]. Although different findings between the experiments are apparent, this work may still suggest a possible transgenerational effect associated with the concentration of prolactin that needs to be explored further.…”
Section: Factors Influencing Maternal Behaviormentioning
confidence: 91%